Activated Carbon Production from Waste Biomass - R, Rajamani.; kumar.B, Vinoth; A, Sujith .; E, Karthick (International Journal of Engineering and Technology, 2018)
Activated carbon is used as filter medium for the removal of hazardous particles in exhaust gases, in the purification of water and also in waste water treatment. Activated carbon is used in gas purification, water purification, sewage treatment and many other applications. This concept is used to satisfy the continuously increasing demand of activated carbon at low cost.The textile industry is one of the largest producers of dye effluent. Treatment of these effluents has to be cost effective hence a number of precursors have been studied as a viable alternative adsorbent. The present work relates to efforts made towards developing a high surface area activated carbon produced from the fruit shells of sterculia foetida by chemical activation process with phosphoric acid as the activating agent the fruit shell of sterculia foetida constitute a novel precursor for the preparation of activated carbon which has not yet been identified as a source for carbon material. Experiments were conducted in lab scale using muffle furnaces under static conditions in a selfâ€“generated atmosphere covering process parameters such as Impregnation Ratio (IR), Carbonization time and Temperature. The process parameters are characterized and optimized based on the Methylene Blue number, Methyl Violet Number and the Iodine number.The adsorption of reactive orange dye onto fruit shell of sterculia foetida activated carbon from aqueous solution was investigated. The process is carried out varying the process parameters as Impregnation Ratio (1:1 to 1:6), Activation Temperature (300 to 800 oC) and Activation Time (60 to 210 min).Â Â Â